Prompt Literacy as an Enhancer of Students' Academic Writing in Higher Education Institutions: A Systematic Literature Review - Plaatjies, Bernadictus O.; Van Wyk, Micheal M. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Prompt literacy has emerged as a pivotal concept in academic writing, particularly within higher education. This systematic literature review (SLR) critically examines and synthesizes research conducted between 2020 and 2025 on using prompting strategies to enhance academic writing among university students. The review aims to identify the types of prompts employed, evaluate their pedagogical effectiveness, explore the contexts of their implementation, and assess the outcomes associated with their use. The SLR followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, encompassing four key stages: data search and collection, selection criteria, data extraction, and data analysis. A two-stage screening process—pre-screening and final eligibility selection—was applied to ensure the inclusion of relevant studies. Findings reveal that 40.5% of the reviewed studies (n=17) adopted a mixed methods research design, reflecting a growing trend toward integrating qualitative and quantitative insights. A central theme across the literature is the critical role of prompt formulation in maximizing the benefits of AI technologies for academic writing. Effective prompts significantly enhanced students' engagement, critical thinking, and writing proficiency. The review also highlights the CLEAR framework as a guiding model for implementing prompting strategies, with implications spanning pedagogical practices, technological integration, and institutional policy development. This review underscores the transformative potential of well-designed prompting strategies in higher education. It calls for a more nuanced understanding of prompt literacy as a foundational skill in the digital age, advocating for targeted interventions and policy support to foster its development. The findings contribute to the growing knowledge of academic writing enhancement and provide actionable insights for educators, instructional designers, and policymakers.